2010
DOI: 10.2174/157016210790442731
|View full text |Cite
|
Sign up to set email alerts
|

Is Metabolic Syndrome Associated to HIV Infection Per Se? Results from the HERMES Study

Abstract: HERMES is a prospective study, including all treatment-naïve patients attending scheduled visits at hospitals in the CISAI group in 2007. The present cross-sectional analysis aims to assess the baseline prevalence and characteristics of Metabolic Syndrome (MS) in a population of HIV-positive treatment-naïve patients. MS was diagnosed using the National Cholesterol Education Program (NCEP) definitions. A total of 292 subjects were enrolled, median age was 37 years, 75% of them were males. The prevalence of MS w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 0 publications
4
32
2
Order By: Relevance
“…5 Similarly, other studies have shown a higher prevalence of metabolic syndrome among HIV-infected individuals with detectable viremia and an increased risk of metabolic syndrome in those with advanced HIV disease (CDC class C, VL > 100,000 or CD4 < 100). 22,31 Therefore, an increased risk of all-cause mortality from metabolic syndrome seen in our cohort may be a reflection of the inter-relationship of systemic inflammation, metabolic abnormalities, and HIV disease.…”
Section: Discussionmentioning
confidence: 82%
“…5 Similarly, other studies have shown a higher prevalence of metabolic syndrome among HIV-infected individuals with detectable viremia and an increased risk of metabolic syndrome in those with advanced HIV disease (CDC class C, VL > 100,000 or CD4 < 100). 22,31 Therefore, an increased risk of all-cause mortality from metabolic syndrome seen in our cohort may be a reflection of the inter-relationship of systemic inflammation, metabolic abnormalities, and HIV disease.…”
Section: Discussionmentioning
confidence: 82%
“…Smoking and alcohol consumption were recorded (detailed description were previously reported [9]) at study entry and end. Information on co-infection with Hepatitis B or C viruses were collected, as well as diagnosis of chronic hepatitis and its cause.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have published the results of the cross-sectional analysis of 292 HAART-naive subjects enrolled in 2007 [9]. Among them, the prevalence of MS was 12.3%, increasing with age and lower education.…”
Section: Introductionmentioning
confidence: 99%
“…92 Patients infected by HIV appear to have higher prevalence of the metabolic syndrome. 93,94 Drug-induced metabolic changes, that include derangement of lipid and glucose metabolism, along with older age, have been associated with increased risk of cardiovascular disease and myocardial infection. 95 Age-related changes in body composition can also influence drug pharmacokinetics by altering drug volume of distribution.…”
Section: Therapy For Hiv Infection and The Problem Of Side Effectsmentioning
confidence: 99%